Ranking the potential carcinogenic hazards to workers from exposures to chemicals that are tumorigenic in rodents. - Gold, L; Backman, G; Hooper, N; Peto, R (1987)
For 41 chemicals there exist both reasonable data on carcinogenic potency in experimental animals and also a defined Permissible Exposure Level (PEL), which is the upper limit of legally permissible chronic occupational exposure for U.S. workers. These 41 agents are ranked by an index that compares the permitted chronic human exposure to the chronic dose rate that induces tumors in 50% of laboratory animals. This index, the Permitted Exposure/Rodent Potency index, or PERP, does not estimate absolute risks directly, but rather suggests the relative hazards that such substances may pose. The PERP values for these 41 substances differ by more than 100,000-fold from each other. The PERP does not take into account the actual level of exposure or the number of exposed workers. Nevertheless, it might be reasonable to give priority attention to the reduction of allowable worker exposures to substances that appear most hazardous by this index and that some workers may be exposed to full-time near the PEL. Ranked by PERP, these chemicals are: ethylene dibromide, ethylene dichloride, 1,3-butadiene, tetrachloroethylene, propylene oxide, chloroform, formaldehyde, methylene chloride, dioxane, and benzene.